The Effect Board Characteristics On Enterprise Risk Management Disclosures: Evidence from State-Owned Enterprise In Indonesia - Kurniawanto, Hudi (Archives of Business Research, 2021)
The purpose of this study is to examine the effect of corporate governance, namely board characteristics on enterprise risk management disclosure. The research object of State-Owned Enterprises listed on the Indonesia Stock Exchange in 2018-2019, with a total sample of 40 annual reports with purposive sampling technique and multiple regression analysis. The results of this study prove that board size no effect on enterprise risk management disclosure, while board independence effect enterprise risk management disclosure. This shows that the commissioners understand and carry out their duties as an independent party in supervising, directing, and evaluating the implementation of corporate governance and corporate strategic policies so that Board Independence in State-Owned Enterprises in Indonesia functions properly.